Shedding light on the last mile: A study on the diffusion of Pay As You Go Solar Home Systems in Central East Africa. (August 2017) - Barrie, Jack; Cruickshank, Heather J.
Abstract: Approximately 1.2 billion people lack basic access to electricity. The United Nations 'Sustainable Energy for All' initiative exemplifies the urgent need to address this issue. Recent advancements in photovoltaic, light emitting diode and battery technology have resulted in the rise of affordable and innovative household electricity technologies, however penetration rates remain low due to complexity surrounding 'last mile' distribution. This paper applies the diffusion of innovations theory as a framework to investigate the 'last mile' challenges encountered when launching a Pay As You Go Solar Home System in a region of Central East Africa. The results indicate that Pay As You Go offers the potential to deliver a disruptive positive impact with regard to increasing access to clean affordable energy for the poor, however, both the technology and business model are more complex than current alternatives and therefore require a much more developed go-to-market strategy. The cost of achieving widespread diffusion is therefore higher than similar products sold at retail, yet this is balanced by potential for a much faster rate of adoption. Finally, this paper demonstrates the applicability of the diffusion of innovations theory as a viable framework for analysing last mile challenges associated with Solar Home Systems. Highlights: First field level study on challenges of scaling Pay as You Go Solar Home Systems; PAYG SHS technology and business model are more complex than current alternatives. Requires a much more developed go-to-market strategy than corresponding products. Potential for a much faster rate of adoption than corresponding products. Diffusion of innovations theory is a viable framework for analysing PAYG SHS.